The Belgian Bone Club 2020 guidelines for the management of osteoporosis in postmenopausal women. (September 2020) - Sanchez-Rodriguez, D.; Bergmann, P.; Body, J.J.; Cavalier, E.; Gielen, E.; Goemaere, S.; Lapauw, B.; Laurent, MR; Rozenberg, S.; Honvo, G.; Beaudart, C.; Bruyère, O.
Highlights: A systematic methodology has been followed to construct the Belgian Bone Club 2020 guidelines. The guideline has been produced taking all management of osteoporosis into account, from screening to monitoring. The BBC 2020 guidelines provide updated algorithms for evidence and consensus-based clinical management of osteoporosis in postmenopausal women. Abstract: Purpose: To provide updated evidence-based guidelines for the management of osteoporosis in postmenopausal women in Belgium. Methods: The Belgian Bone Club (BBC) gathered a guideline developer group. Nine "Population, Intervention, Comparator, Outcome" (PICO) questions covering screening, diagnosis, non-pharmacological and pharmacological treatments, and monitoring were formulated. A systematic search of MEDLINE, the Cochrane Database of Systematic Reviews, and Scopus was performed to find network meta-analyses, meta-analyses, systematic reviews, guidelines, and recommendations from scientific societies published in the last 10 years. Manual searches were also performed. Summaries of evidence were provided, and recommendations were further validated by the BBC board members and other national scientific societies' experts. Results: Of the 3840 references in the search, 333 full texts were assessed for eligibility, and 129 met the inclusion criteria. Osteoporosis screening using clinical risk factors should be considered. Patients with a recent (<2 years) major osteoporotic fracture were considered at very high and imminent risk of future fracture. The combination of bone mineral density measured by dual-energy X-ray absorptiometry and 10-year fracture risk was used to categorize patients as low or high risk. Patient education, the combination of weight-bearing and resistance training, and optimal calcium intake and vitamin D status were recommended. Antiresorptive and anabolic osteoporosis treatment should be considered for patients at high and very high fracture risk, respectively. Follow-up should focus on compliance, and patient-tailored monitoring should be considered. Conclusion: BBC guidelines and 25 guideline recommendations bridge the gap between research and clinical practice for the screening, diagnosis, and management of osteoporosis.